Essential Oil Yield, Composition, and Bioactivity of Sagebrush Species in the Bighorn Mountains - Valtcho D. Zheljazkov; Charles L. Cantrell; Ekaterina A. Jeliazkova; Tess Astatkie; Vicki Schlegel (Plants, 2022)
Sagebrush (Artemisia spp.) are dominant wild plants in large areas of the U.S., Canada and Mexico, and they include several species and subspecies. The aim was to determine if there are significant differences in essential oil (EO) yield, composition, and biological activity of sagebrush within the Bighorn Mountains, U.S. The EO yield in fresh herbage varied from 0.15 to 1.69% for all species, including 0.25–1.69% in A. tridentata var. vaseyana, 0.64–1.44% in A. tridentata var. tridentata, 1% in A. tridentata var. wyomingensis, 0.8–1.2% in A. longifolia, 0.8–1% in A. cana, and 0.16% in A. ludoviciana. There was significant variability in the EO profile between species, and subspecies. Some EO constituents, such as α-pinene (0–35.5%), camphene (0–21.5%), eucalyptol (0–30.8%), and camphor (0–45.5%), were found in most species and varied with species and subspecies. The antioxidant capacity of the EOs varied between the species and subspecies. None of the sagebrush EOs had significant antimicrobial, antimalarial, antileishmanial activity, or contained podophyllotoxin. Some accessions yielded EO with significant concentrations of compounds including camphor, eucalyptol, cis-thujone, α-pinene, α-necrodol-acetate, fragranol, grandisol, para-cymene, and arthole. Therefore, chemotypes can be selected and possibly introduced into culture and be grown for commercial production of these compounds to meet specific industry needs.